Various pAQU plasmids possibly contribute to disseminate tetracycline resistance gene tet(M) among marine bacterial community - Nonaka, Lisa; Maruyama, Fumito; Onishi, Yuki; Kobayashi, Takeshi; Ogura, Yoshitoshi; Hayashi, Tetsuya; Suzuki, Satoru; Masuda, Michiaki (Frontiers in Microbiology, 2014)
Emergence of antibiotic-resistant bacteria in the aquaculture environment is a significant problem for disease control of cultured fish in as well as in human public health. Conjugative mobile genetic elements (MGEs) are involved in dissemination of antibiotic resistance genes (ARGs) among marine bacteria. In the present study, we first designed a PCR targeting traI gene encoding essential relaxase for conjugation. By this new PCR, we demonstrated that five of 83 strains isolated from a coastal aquaculture site had traI-positive MGEs. While one of the five strains that belonged to Shewanella sp. was shown to have an integrative conjugative element of the SXT/R391 family (ICEVchMex), the MGEs of the other four strains of Vibrio spp. were shown to have the backbone structure similar to that of previously described in pAQU1. The backbone structure shared by the pAQU1-like MGEs in the four strains corresponded to a ~100-kbp highly conserved region required for replication, partition and conjugative transfer, suggesting that these MGEs are plasmids that constitute “pAQU group”. The pAQU group plasmids were shown to be capable of conjugative transfer of tet(M) and other ARGs from the Vibrio strains to E. coli. The pAQU group plasmid in one of the examined strains was designated as pAQU2, and its complete nucleotide sequence was determined and compared with that of pAQU1. The results revealed that pAQU2 contained fewer ARGs than pAQU1 did, and most of the ARGs in both of these plasmids were located in the similar region where multiple transposases were found, suggesting that the ARGs were introduced by several events of DNA transposition into an ancestral plasmid followed by drug selection in the aquaculture site. The results of the present study indicate that the “pAQU group” plasmids may play an important role in dissemination of ARGs in the marine environment.